The effect of the board of directors characteristics on firm performance of Iraq listed companies: A conceptual framework - Jedi, Firas Farhan; Nayan, Sabri (2017)
Purpose - Economies all over the world need the effective and efficient performance of business units both financial and non-financial firms because they are the engine of economic development of nations. Furthermore, many companies around the world try to improve their performance for the purpose of getting fund from investors in order to expand and grow. On the other hand, investors need to have confidence that the company is being well managed and will continue to be profitable investments. However, the performance of Iraq listed firms is discouraging given the declining nature of its price index performance from 2011 to 2015. The poor performance of listed firms around the world has been attributed to ineffective CG. Therefore, the effect of board of directors’ structure on firm performance is among the corporate governance primary mechanism which drawn the attention of many researchers and scholars for many decades.Despite this, the discussion has given little attention to the influence of salient board characteristics on firm performance. Furthermore, there is a lack of prior studies that examine these relationships in the developing countries such as Iraq.The aim of this paper is to propose a framework that will investigate if the salient board characteristics influence firm performance of Iraqi listed companies.Therefore, this paper offers a preposition on the association between board member gender, board members’ educational level, government link of the board, board meeting, experience of the board, board independence, board size and firm performance. Moreover, the proposed study will contribute in bridging the identified gap and enrich the existing literature.The board of directors, which is one of the most important mechanisms for corporate governance (Fernández-Gago, Cabeza-García, & Nieto, 2016).Importantly, the board of directors is regarded as the principal internal mechanism that can be used to monitor executive decisions (Al Manaseer, Al-Hindawi, Al-Dahiyat, & Sartawi, 2012).Similarly, the board occupies an important position in CG mechanisms through which the shareholders can control the top management (John & Senbet, 1998).Moreover, the board is a mechanism that is used to determine the firm’s strategy, and to ensure that enough measures are in place to protect the value of the shareholder (Keenan, 2004).In this regard, it is theobjective of this study to substantially contribute to corporate governance literature by unveiling and proposing additional characteristics of board of director characteristics such as, the board size, board independence, board meeting, board members educational level, board member gender, government link of the board, as all of these may lead to enhance the performance of the company (Arora & Sharma, 2015; Bhagat, Bolton, & Subramanian, 2010; Bantel & Jackson, 1989; Cheng, 2008; Coles, Daniel, & Naveen, 2008; Gottesman & Morey, 2006; Wiersema & Bantel, 1992) .Even though some of the variables have been discussed by the past scholars, majority of the literature emanated from developed nations and of which their results may not generalizable and applicable to the Middle East countries in general and Iraq in particular.Methodology - This article is conceptual which makes a preposition on an empirical work using a secondary data and analysed using a Dynamic GMM methods